A case of COVID‐19 with pernio‐like skin lesions and increased red blood cell distribution width - Satoko Minakawa; Yasushi Matsuzaki; Akari Terada; Shu Ogasawara; Yuki Nishiya; Jin Irie; Yoshiya Ishizawa; Hiroyuki Hanada; Daisuke Sawamura (Journal of Cutaneous Immunology and Allergy, 2023)
Heparin resistance has been observed in patients with active severe COVID‐19 infection. The red blood cell distribution (RDW), a component of the complete blood count that reflects cellular volume variation, has been shown to be associated with elevated risk for morbidity and mortality in a wide range of diseases. Cutaneous manifestations, RDW, and levels of LD and D‐dimer might be useful biomarkers in triage of patients with COVID‐19.